MAKING PUNISHMENT PAY: The Political Economy of Revenue, Race, and Regime in the California Prison Boom. (9th February 2015) - Hagan, John; Plickert, Gabriele; Palloni, Alberto; Headworth, Spencer
Abstract: Sociologists have neglected the politically channeled and racially connected role of leveraged debt in mass incarceration. We use qualitative and quantitative data from California, circa 1960–2000, to assess how Republican entrepreneurial leveraging of debt overcame contradictions between parochial preferences for punishment and resistance to paying taxes for building prisons. The leveraging of bond debt deferred and externalized the costs of building prisons, while repurposed lease revenue bonds massively enlarged and extended this debt and dispensed with the requirement for direct voter approval. A Republican-dominated punishment regime capitalized debt to build prisons in selected exurban Republican California counties with growing visible minority populations. We demonstrate that the innovative use of lease revenue bonds was the essential element that enlarged and extended funding of California prison construction by an order of magnitude that made this expansion a boom. With what Robert Merton called the consequences of imperious interest, this prison expansion enabled the imprisonment of an inordinately large and racially disproportionate inmate population.